THU0458 Assessment of dietary calcium intake among rheumatology patients. (23rd January 2014) - Grapton, X.; Leclere, D.; Lemesle, P.; Poulain, L.; Renard, P.
Abstract : Objectives: Our patients are influenced by all medical information, and even rumours. The aim of this study is to analyse their habits and reactions concerning dairy products and calcium. Methods: 305 patients completed a questionnaire in the waiting room of non-hospital-based rheumatologists. 90% were women, while the average age was 62 years and 97% were from the île-de-France region. 33.6% took osteoporosis medication or a vitamin and calcium supplement. 66% underwent a bone densitometry test (17.4% for osteopenia, 13% for osteoporosis). 24% had a history of non-traumatic fracture and 13% had another osteoporosis risk factor. 32% practised a weight-bearing sport, while 12.5% had lost more than 8kg through diet. Results: 80% of those questioned did not know the body's calcium or nutritional requirements apart from dairy products in content, but believe they have a sufficient intake. Nutritional calcium intake is mainly via yoghurts (37%). 56.4% have a nutritional calcium intake of <900 mg/day. 22% of patients drink calcium-enriched water. 25% of those questioned think that soya milk has the same benefits as cow's milk and use it instead of cow's milk half the time. Those with a BMI of less than 19 have the lowest nutritional calcium intake (740 mg/day on average). 40-60-year-old patients are the most responsive to rumours and lectures on milk. They are the ones who change their nutritional habits with regard to dairy products. Before the age of 40 years, patients are less responsive to medical advice and are influenced by the cost of dairy products and advertising. Less than 10% of those questioned have no dairy intake because of taste, fat content, high cholesterol concerns and intolerances. In 25% of cases, lectures and rumours created a mistrust of dairy products due to contradictory advice. Two thirds consider them useful while one third fear them. Calcium is not dangerous (63%) but can lead to disorders if taken in excess. The dairy products-calcium-osteoporosis relationship is well-understood, yet the onset of a fracture does not change people's habits concerning calcium (71%). Bone density measurement results and medical advice have a strong impact (91%). The effects of tobacco, alcohol and salt on bones is not well-known. 52% are ignorant of the role of vitamin D for the bones, but do relate it to calcium. Conclusions: While campaigns for the consumption of dairy products have helped promote their relevance in bone health, they have not dispelled any concerns over gaining weight or worsening cholesterol levels. Calcium is widely approved <73%>89%> whatever the age to maintain bone quality (41%) and fight osteoporosis (28%). Osteoporosis and the risk of fracture are well-understood, which presupposes that there is a determination to fight both. Disclosure of Interest: None Declared